Rola mechanizmu oksydacyjnego w patogenezie zwyrodnienia siatkówki związanego z wiekiem (AMD) - Nowak, Mariusz; Marek, Bogdan; Kos-Kudła, Beata; Kajdaniuk, Dariusz; Głogowska-Szeląg, Joanna (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
Oxidative stress, are believed to be an important factor in the pathogenesis of age related diseases e.g. age related macular degeneration (AMD) and age related cataract. The is strong evidence suggesting that antioxidants can protect against development of this diseases, how ether experimental and clinical data have often been inconsistent. In this paper authors presents the review of the literature concerning on the connections between oxidative mechanisms and AMD and protective role of the antioxidative vitamin and other antioxidative factors supplementation in this disorder. This publication tries to estimate the anti-pericyte autoantibodies role in progression of diabetic retinopathy.